1971
DOI: 10.1192/bjp.118.545.471
|View full text |Cite
|
Sign up to set email alerts
|

Depression: Defence Mechanisms in Speech

Abstract: Weintraub and Aronson have described a method for the study of Psychological Defence Mechanisms through verbal behaviour analysis in psychiatric patients and controls (Weintraub and Aronson, 1962, 1964, 1965 and 1967). In this study we have re-tested their method on a group of middle-aged English depressed patients and matched surgical controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

1980
1980
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…counting from one to ten (16-18, 25-27); "free" or "spontaneous" speech in which the patient either is asked to speak on a topic for a certain amount of time (e.g. 28) or is subjected to a semistructured interview (e.g. 29); or reading aloud (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…counting from one to ten (16-18, 25-27); "free" or "spontaneous" speech in which the patient either is asked to speak on a topic for a certain amount of time (e.g. 28) or is subjected to a semistructured interview (e.g. 29); or reading aloud (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…in empirical research, reduced rate or tempo of spontaneous speech in depression is a frequently reported finding and seems to be a stable phenomenon (e.g., Hinchliffe, Lancashire, & Roberts, 1971;Mandal, Srivastava, & Singh, 1990;Newman & Mather, 1938;Pope, Blass, Siegman, & Raher, 1970;Weintraub & Aronson, 1967; see review by Siegman, 1987a). Because the temporal variables are net consistently defined, it is not clear to what extent speech rate is affected by pause time.…”
Section: Temporal Aspects Of Speech and Depressionmentioning
confidence: 96%
“…Because the temporal variables are net consistently defined, it is not clear to what extent speech rate is affected by pause time. The empirical studies that have focused on the number and duration of pauses in depressive speech have yielded somewhat inconsistent results, although there are a large number of studies that report pause lengthening in depressive state (Andreasen, Alpert, & Martz, 1981;Breznitz, 1992;Darby, Simmons, & Berger, 1984;Kuny & Stassen, 1993;Nilsonne, 1987;Hinchliffe et al, 1971;Pope et al, 1970;Stassen, Bomben, & Giinther, 1991;Vanger, Summerfield, Rosen, & Watson, 1992;Weintraub & Aronson, 1967). Some of the discrepancies in the findings in this area are due to widely varying criteria used in the definition of speech pauses (for example, time periods varying between two to five seconds have been used as criteria for the identification of silent pauses).…”
Section: Temporal Aspects Of Speech and Depressionmentioning
confidence: 97%
“…1984;Blackburn. 1975: Bouhuys andMulder-Hajonides, 1984;Bouhuys and Al berts, 1984;Godfrey and Knight, 1984;Greden et al, 1981: Hardy et al, 1984Helfrich et al, 1984: Hinchcliffe et al, 1971Darby, 1979: Johnson et al. 1986;Klos andEllgring, 1984: Newman andMather.…”
Section: Introductionunclassified